(untitled) (Baghdad Science Journal, 2025)
A metal mandrel was designed for manufacturing the cathodes of high power electron tube ( Tetrode ) used in broadcasting transmitting tubes type TH558 and CQS200.The cathodes were manufactured in the present work from thoriated tungsten wires ( 2? ThO2- W) with different diameters .These cathodes were carbonized in sequences of processes to determine the carbonization parameters (temperature, pressure, time, current and voltage).Then the carbonized cathodes dimension were accurately measured to determine the deviation due to the high temperature distortion effect at about 1800°C .the distorted cathodes due to the carbonization process was treated when it was subjected inside the vacuum chamber and heat treated again .The carbonized cathode distortions as a function of temperature were measured in the range of (1500°C-1800°C).The temperature was determined using an optical pyrometer and also calculated using Stephan’s-Boltzmann relation.